Valor de la razón neutrófilo - linfocito como predictor de mortalidad en pacientes con neumonía adquirida en la comunidad. Hospital Regional Docente de Trujillo - Rocca Carranza, Roberto David (2020)
Community-acquired pneumonia (CAP) is a major problem with significant morbidity, mortality, and cost; incidence has not decreased in recent decades, despite advances in supportive care. Patients with pneumonia are also at risk of developing complications such as the need for mechanical ventilation for hypoxemic respiratory failure, the need for vasopressors for hemodynamic instability, and failure of the multi-organ system. Neutrophil to lymphocyte ratio (NLR), as an accessible biomarker, has shown that NLR is proposed as an independent predictor of poor survival in various clinical circumstances, one of the most convincing explanations is mainly based on the physiological link between neutrophilia and lymphopenia with systemic inflammation and stress; In this sense, there is a growing interest in relation to the use of indicators that allow assessing the prognosis of patients with CAP as early as possible and having identified investigations that attribute a prognostic character to the information provided by the leukocyte count and its ifferential formula, considering that the Assessment of these parameters is carried out routinely in routine clinical practice and it is also easy to define with respect to other scales with similar functions and also considering that we have not identified similar studies in our setting. Type of Research: analytical, observational, prospective, cross-sectional, diagnostic tests. Objective: To determine if the neutrophil lymphocyte ratio has value as a predictor of mortality in patients with community-acquired pneumonia at the Trujillo Regional Teaching Hospital. Location and Institution where the Academic Work will be developed: Regional Teaching Hospital of Trujillo - Trujillo - La Libertad. Duration: From October 1, 2018 to September 30, 2019. Funding: Author's own. Material and Methods: Adults with a diagnosis of CAP will be identified in the Emergencies service of the Trujillo Regional Teaching Hospital who meet the inclusion criteria; the individuals belonging to the study will be selected by simple random sampling based on their survival condition at discharge to group them in each of the study groups, the pertinent data corresponding to the necessary items will be collected to be able to characterize the score of the Neutrophil lymphocyte ratio for each patient, which will be incorporated into the data collection sheet according to annex 1. Data Analysis: The data record that will be onsigned in the corresponding collection sheets will be processed using the SPSS 23 statistical package.